2021
DOI: 10.15240/tul/001/2021-03-004
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Financial Structure in Agriculture, Forestry and Fishing Industry in Selected Countries of Central and Eastern Europe

Abstract: Every economic sector, every single industry, every economy, and even every firm has its specific financial structure. Given that it is not possible to examine thousands of individual companies for scientific purposes, it is necessary to at least examine the differences between individual sectors, industries and countries. At the same time, the formation and optimization of the financial structure is influenced by a myriad of diverse factors that financial managers should take into account in their decisions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In the monitored publications, the keyword capital structure is found in 4,111 articles, which means that approximately 70% of all publications related to capital structure issues contain this keyword. Ruckova and Skulanova (2021) state that the development of the capital structure depends on the conditions of individual enterprises, especially the assets' structure, ownership structure, profitability indicators and many other economic performance indicators. At the same time, it is the result of the operation of the external business environment, determined by the macroeconomic, legislative, and institutional framework conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the monitored publications, the keyword capital structure is found in 4,111 articles, which means that approximately 70% of all publications related to capital structure issues contain this keyword. Ruckova and Skulanova (2021) state that the development of the capital structure depends on the conditions of individual enterprises, especially the assets' structure, ownership structure, profitability indicators and many other economic performance indicators. At the same time, it is the result of the operation of the external business environment, determined by the macroeconomic, legislative, and institutional framework conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Zafar et al [17], Song [18], Jovanovic [19], Samarakoon et al [20], and Singh [21] calculated the panel data for leverage, such as a dependent variable, explained with internal enterprise financial parameters. R ůčková and Škulá ňová [22] analysed the capital structure determinants for the agriculture, forestry, and fishing industries in Central and Eastern Europe. The authors studied these three sectors together based on data for the period of 2009-2016.…”
Section: Literature Review On Capital Structure Determinantsmentioning
confidence: 99%
“…These authors used determinants of the capital structure or the leverage of different companies as explanatory variables in the panel data model along with external economic variables. Some macroeconomic elements were also previously included, such as those in the works by De Leon and Kanwal [29], Nadeem [30], and R ůčková and Škulá ňová [22]. According to the lack of up-to-date panel data research on the capital structure of forestry in Central and Eastern European countries, the current study is aimed at improving knowledge on leverage determinants.…”
Section: Literature Review On Capital Structure Determinantsmentioning
confidence: 99%
“…Identifying the determinants that lead to the growth of companies will ensure the development of this sector, providing an incentive to reduce imports and increase exports, which will certainly have a positive impact on the economic growth of European countries. Research conducted by R ůčková and Škulá ňová showed that companies in agriculture, forestry, and fisheries industries in seven countries of central and eastern Europe primarily decided to finance from their own sources in a period of economic growth when profit growth most often occurs [9].…”
Section: Introductionmentioning
confidence: 99%